Yields response and quality of Naruto sweet potato (Ipomoea batatas L.) to nitrogen and kalium fertilizer application - Siwi Hardiastuti Endang Kawuryan; Heti Herastuti (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2012)
The purpose of this experiment was to determine the best nitrogen and kalium fertilizer dosage to increase yields and quality of sweet potato. The experiment was conducted at Bandongan Kulon, Ngablak, Magelang, Central Java Province during the period of May up to October 2005, on latosol soil and 1,300 m height. A factorial experiment of 3×3 factors was employed, where the treatments were arranged in Randomized Block Design with three replicates. The first factor was nitrogen fertilizer dosage that consisted of three levels, i.e.: 46 kg N/ha equal with 100 kg Urea/ha, 92 kg N/ha equal with 200 kg Urea/ha and 138 kg N/ha equal with 300 kg Urea/ha. The second factor was kalium fertilizer dosage that consisted of three levels, i.e.: 60 kg N/ha equal with 100 kg KCl/ha, 120 kg N/ha equal with 200 kg KCl/ha and 180 kg N/ha equal with 300 kg KCl/ha. The result of the research showed that no interaction between nitrogen and kalium fertilizer dosage on the number of tuber per plant, weight of tuber per plant and weight of tuber per sample, but they increased yields quality significantly. Nitrogen 92 kg/ha and Kalium 180 kg/ha produced the highest sucrose contents, Nitrogen fertilizer 138 kg/ha and Kalium fertilizer 60 kg/ha produced the highest tuber starch, Nitrogen fertilizer 46 kg/ha and Kalium fertilizer 120 kg/ha produced the highest β–karoten.Keywords: Nitrogen, kalium, fertilizer, sweet potato